Патримонизация святых мест в Западном Казахстане и воспитание «поколения Независимости» (Journal of Philosophy Culture and Political Science, 2019)
The article considers the history of preservation and recreation of the historical originality of price- less works – monuments of mausoleums and architectural art of the Kazakh people, including Western Kazakhstan. The accession of Kazakhstan to independence marked the beginning of a number of pro- cesses that continue to evolve. They affect various aspects of the life of the state and the people. The current culture of Kazakhstan is characterized by the preservation and development of the tradi- tions of previous generations, the discovery of new historical and cultural monuments, the enhancement of conservation, the restoration of mausoleums, ancient mosques, ancient settlements and the creation of new museums, historical and cultural reserves. The article was written in the framework of the research project «Multidimensional study of the history, problems and prospects for the implementation of international educational projects in the Re- public of Kazakhstan» on grant funding from the Ministry of Education and Science of the Republic of Kazakhstan. The purpose of the study is to comprehensively analyze and reconstruct the system of representa- tions of the nomads of the Kazakhs associated with the ritual activity and reflected in specific archaeo- logical sites. The research methodology is based on the principles of historical knowledge and includes a system of general philosophical and general historical laws of the development of society, individual processes and phenomena. The results of research work are cultural and historical heritage is an integral part of the concept of «living environment», which refers to the phenomena of the external world included in the life of the subject. The preservation of heritage is possible only if it becomes an element of the living environment, is included in the daily life of a person.Key words: holy places, ancient mausoleums, Kazakhstan, spiritual tradition.